Evidence-based policing in Australia: an examination of the appropriateness and transparency of lineup identification and investigative interviewing practices - Cullen, Hayley J. (International journal of police science & management, 2021)
Psychological research has been pivotal in influencing the way police forces globally approach and undertake criminal investigations. Increasing psychological research in recent years has led to the development of best-practice guidelines for conducting police investigations, across a number of key areas of criminal investigation. For example, procedures for creating and conducting lineups as recommended by the American Psychology-Law Society, and the UK-developed PEACE model for investigative interviewing, have both been of influence in Australia. However, the extent to which these evidence-based recommendations have been incorporated into policing practice within Australia is unclear. In this article, we conducted an exploratory review of publicly available policing documents within Australian states and territories, to determine the extent to which best practice lineup identification and investigative interviewing procedures have been adopted into police practice. The review revealed that for lineup identification procedures, many of the basic recommendations for conducting lineups were not incorporated into publicly available policing manuals. For investigative interviewing, it appeared on the surface that elements of the PEACE model were implemented within most Australian jurisdictions, albeit this was often not explicitly stated within policing documents. A key issue identified was a lack of (understandable) public transparency of policing procedure, as a number of Australian jurisdictions failed to have publicly available policing manuals or handbooks against which to evaluate their procedures. Therefore, we argue that there is a need for better collaboration between researchers and law enforcement in order to achieve evidence-based, transparent policing within Australia.